The influence of French aesthetics on Francesc Mirabent - Carcasó, Jordi (Journal of Catalan Intellectual History, 2013)
The importance of English and Scottish Philosophy for Catalan Philosophy has often been a subject of study, whilst another more powerful influence has very seldom been noted: French Philosophy. Francesc Mirabent’s aesthetics, in particular, are established in an intense relationship with the professors at the University of Sorbonne, through whom he will be able to penetrate the European debate on aesthetics. We have attempted to briefly determine the thematic links that bond Francesc Mirabent with the principal French aesthetes in the 20th century. key words: Francesc Mirabent, French aesthetics.